Preserving Dutch colonial hegemony through incorporated islamic matrimonial system in the Netherlands East Indies - Entol Zaenal Muttaqin; Ahmad Zaini (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
The growth of Islamic matrimonial system in the present Indonesia was originally formulated in the 19th century of the Netherlands colonialism. There are several discourses among Dutch scholars in establishing an applicable law system since there are various legal system existed, and finally the colonial government issued legal dualism in order to preserve their hegemony. Provoked by several scholars the new constitution in 1854 was approved. In that, the Islamic matrimonial system was assimilated into Adat law and therefore the Islamic marriage system was allowed to be practiced in its own way. This Islamic matrimonial system was formed as a law under Dutch controls. Accordingly, the paper discusses Dutch hegemony system through applicable Islamic matrimony, and the development of this marriage as the formation of preserving hegemony. This paper arguably investigates Dutch hegemony system through applicable of Islamic matrimony. The analysis is guided by following questions: first, what are the reasons behind the implementation of indigenous legal institution such as Islamic marriage in preserving hegemony? Second, to what extent does the Islamic matrimony persisted within the applicable policy? The methodology is critical analysis of legal history contents, the data mainly taken from legal manuscripts which is a comprehensive view of law from a particular critical vantage point: a way of doing law, perhaps doing things with law. This paper argued that Dutch Hegemony system is poles apart from many colonialism regimes, the incorporated of indigenous legal system has become a method to subjugate indigenous power. Therefore, Islamic Matrimony developed into ways according to colonial’s interest